The Influence Of Leadership Style And Work Motivation On The Performance Of Angkasa Garden Hotel Pekanbaru Employees - Lukina, Teresa; Mairiza, Diany; Erman, Nilam (Journal of Economic, Management, Business, Accounting Sustainability, 2024)
The purpose of this research is to determine the influence of leadership style and work motivation on employee performance at Angkasa Garden Hotel Pekanbaru. The sample in this research was 44 employees of Angkasa Garden Hotel Pekanbaru. Meanwhile, the variables examined in this research are leadership style, work motivation and employee performance. Data analysis uses the multiple linear regression method using validity, reliability, normality tests, multicollinearity tests, heteroscedasticity tests, t tests, f tests, and R2 tests. This test is carried out to determine the relationship between the independent variable and the related variable (dependent variable). Based on the research results, service quality simultaneously influences student satisfaction with a correlation value of R = 0.387, which shows that there is a close relationship between leadership style and work motivation and the performance of Angkasa Garden Hotel Pekanbaru employees. Meanwhile, R square was found to be 0.150, which means leadership style and work motivation contributed 38.7% to the performance of Angkasa Garden Hotel Pekanbaru employees. Partially, it was found that the leadership style and work motivation variables had a positive and significant effect on the performance of Angkasa Garden Hotel Pekanbaru employees with t count 2.810> t table 2.018 with a significance level of 0.000 which is smaller than alpha 0.05. The simple linear regression equation is as follows: Y= -3.249 + 0.063X1 + 0.088X2 + e